Technology blueprint: Budu Dispenser / Nik Nur Syazreen Nik Rohaimi…[et al.] - Nik Rohaimi, Nik Nur Syazreen; Abdul Kadir, Syahirah; Mohd Rodzi, Nabila Husna; Mohd Zaki, Nur Shahirah; Abdul Rahman, Nur Najihah Izyan (2020)
The “Budu” Dispenser machine is an innovation made that are available in the market. As in the market nowadays only the machine that can process the “budu” only but cannot transfer it from “Tempayan” to the Squeezer machine. Therefore, we have created a machine that can transfer and process the “Budu” automatically. This machine can reduce the number of manpower used, save energy and time. Not just that this machine is affordable as it is design for the “Budu” entrepreneurs with small scale